Cu2O/InGaN heterojunction thin films with enhanced photoelectrochemical activity for solar water splitting. (August 2020) - Alizadeh, Mahdi; Tong, Goh Boon; Qadir, Karwan Wasman; Mehmood, Muhammad Shahid; Rasuli, Reza
Abstract: We study Cu2 O/InGaN heterojunction thin films with different thicknesses of Cu2 O layer as a photoanode in photoelectrochemical (PEC) water splitting cell. Results show that the bandgap energy of Cu2 O/InGaN heterojunction thin films is 2.60–2.72 eV and, according to Vegard's law, the indium content of the InGaN thin film is 22%. Electrochemical impedance spectroscopy shows the charge-transfer resistance value of about 0.4 kΩ for the optimized sample revealing enhanced charge separation and transfer at the interface. A maximum photocurrent density of 0.16 mA cm −2 at 0.5 V vs. Ag/AgCl was obtained for the Cu2 O/InGaN heterojunction thin films with an overall thickness of 250 nm. The obtained value is 4.2 and 3.2 times higher than that of pure InGaN and Cu2 O thin films photoanodes, respectively. We showed charge separation mechanism in the Cu2 O/InGaN heterojunction photoelectrodes. According to our model, gradient energy bandgap reduce the recombination rate of photo-induced electron-hole pairs, and significantly enhance the PEC performance. Highlights: Cu2 O/InGaN heterojunctions thin films were grown by MOCVD and sputtering methods. Cu2 O layer on InGaN thin films significantly improved the photocurrent density. Photocurrent density of optimized InGaN/Cu2 O is 4.2 times higher than that of InGaN. The charge-transfer resistance value of 0.4 kΩ was obtained for optimized sample. Enhanced charge separation at the interface were deduced from the band structure.